Xenophyllum juniperinum (Compositae, Senecioneae), a new required combination - Calvo, Joel; Muñoz-Schick, Mélica; Moreira-Muñoz, Andrés (Phytotaxa, 2017)
Due to ongoing studies on the austral species of Xenophyllum and Werneria, we noticed that some taxonomic and nomenclatural adjustments are required. Herein, we propose a new combination, Xenophyllum juniperinum.